2009
DOI: 10.2353/ajpath.2009.090076
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase-1 Associates with Integrin αVβ3 to Mediate Endothelial Cell Survival

Abstract: 3 ECM and GF-induced survival signals involve integrins, a family of transmembrane heterodimeric cell surface proteins that are formed by two noncovalently associated subunits, ␣ and ␤. Integrins exist in two distinct functional states, an inactive nonadhesion-promoting state and a ligand-bound, active, and adhesion-promoting conformation. 4 On ligand binding, integrins are aggregated in transmembrane complexes (focal contacts) that are enriched in cytoskeletal proteins (eg, talin and vinculin) as well as sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…18 We have recently demonstrated a requirement of SK-1 phosphorylation at serine 225 for increased heterotrimeric complex formation between SK-1, ␣ v ␤ 3 and CD31 following factor deprivation where ␣ v ␤ 3 activation and subsequent EC survival signals include the Bcl-X and nuclear factor B pathways. 19 Herein we demonstrate, for the first time, that SK-1 is integral for TNF␣-induced ␣ 5 ␤ 1 activation, Ang-2 expression and neutrophil adhesion under shear flow. Whether phosphorylation of SK-1 is also involved in this process is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 We have recently demonstrated a requirement of SK-1 phosphorylation at serine 225 for increased heterotrimeric complex formation between SK-1, ␣ v ␤ 3 and CD31 following factor deprivation where ␣ v ␤ 3 activation and subsequent EC survival signals include the Bcl-X and nuclear factor B pathways. 19 Herein we demonstrate, for the first time, that SK-1 is integral for TNF␣-induced ␣ 5 ␤ 1 activation, Ang-2 expression and neutrophil adhesion under shear flow. Whether phosphorylation of SK-1 is also involved in this process is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition was not observed with the ␣ v ␤ 3 blocking antibody (LM609) (Figure 6B), an integrin also activated by SK-1. 19 As TNF␣ is also known to regulate VCAM-1 and ICAM-1 expression on HUVECs via SK-1, 20 we next investigated their contribution to ␣ 5 ␤ 1 -mediated leukocyte adhesion. As shown in Figure 6B, antibodies to ␣ 5 ␤ 1 , VCAM-1 and ICAM-1, alone, or together, demonstrated a similar level of inhibition.…”
Section: Tnf␣-induced Activation Of ␣ 5 ␤ 1 On Huvecs Mediates Leukocmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, two mammalian isozymes, SphK1 and SphK2, have been characterized. It is widely accepted that SphK1 resides at the centre of a cell-survival rheostat that balances the cellular levels of pro-apoptotic ceramide with anti-apoptotic S1P (2,3). Evidence also showed that SphK1 enhances cancer cell migration by secretion of S1P in a protein kinase C-α-and ERK1̸2-dependent manner (4).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the localization of SK-1 and SK-2 differs with SK-1 being predominantly found in the cytoplasm and at the plasma membrane leading to prosurvival effects [61, 62], and SK-2 being predominantly found in the nucleus and at the endoplasmic reticulum (ER) promoting proapoptotic effects [63, 64] (Figure 3). Three splice isoforms of SK-1 have been identified (i.e., SK-1a, SK-1b, and SK-1c) that differ at their N-termini with additional 14 and 86 amino acids in SK-1b and SK-1c, respectively [65].…”
Section: Sphingosine Kinasementioning
confidence: 99%